1990
DOI: 10.1128/mcb.10.3.1234
|View full text |Cite
|
Sign up to set email alerts
|

Members of the 70-kilodalton heat shock protein family contain a highly conserved calmodulin-binding domain.

Abstract: The 70-kilodalton heat shock protein (hsp7O) family members appear to be essential components in a number cellular protein-protein interactions. We report here on the characterization of a new functional region in hsp7O, a calmodulin-binding site. We have identified a 21-amino-acid sequence within the hsp7O protein that contains a calmodulin-binding domain. The peptide formed a potential amphipathic alpha helix and bound calmodulin with high affinity. Comparison of amino acid homology of this calmodulin-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…Horseradish peroxidase (HRP)-conjugated secondary antibodies were purchased from Invitrogen. Pan-HSP70 antibody was created in-house as previously described (24).…”
Section: Methodsmentioning
confidence: 99%
“…Horseradish peroxidase (HRP)-conjugated secondary antibodies were purchased from Invitrogen. Pan-HSP70 antibody was created in-house as previously described (24).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Ca 2+ ions which inhibit the ATPase, stimulate the autophosphorylation activity, indicating a regulatory role of Ca 2+ (CEGIELSKA and GEORGOPOULOS 1989). The existence of a highly conserved calmodulin-like binding domain in various members of the hsp70 family may be of relevance in this context (STEVENSON and CALDERWOOD 1990).…”
Section: Dnak-the Prokaryotic Homologuementioning
confidence: 99%
“…Previous reports have shown that members of the Hsp70 family bind CaM in a calcium-dependent manner (Stevenson and Calderwood 1990). Heat shock could increase intracellular Ca 2+ levels and promote the association CaM and Hsp70 (Rocak and Linder 2004;Drummond et al 1986).…”
Section: Discussionmentioning
confidence: 99%